APPLICATION OF INFORMATION SERVICES TO IMPROVE GOOD CHARACTER IN CLASS X STUDENTS AT SMA NEGERI 10 MEDAN - Morisca, Aulia; Nur, Zaharuddin (BRIGHT VISION Journal of Language and Education, 2023)
In general, the age of students is the age of character formation. The better the child's character, the more advanced his educational thinking and behavior will be. Character is what must be prioritized in schools, because character aims to shape humans into an advanced and modern era, character also encourages a developing mindset. Information services are services that attempt to cover individual deficiencies in required information. The aim of this research is to improve good character in class The research technique used was a simple random sampling technique, in two cycles, where the first cycle was planning and ended with the second cycle with the evaluation stage. Meanwhile, to obtain information data from the results of this research, the researcher used a questionnaire distribution which will be a comparison of before the service was implemented and after the service was implemented, which is in the form of a simple percentage. . The results of distributing and collecting questionnaire data in the first cycle were with an average value of 63.81 (low), then distributing and collecting questionnaire data again in the second cycle with an average value of 96.06 (high), it can be understood that the implementation of the service Information to Improve Good Character in Students at SMA Negeri 10 Medan for the 2022/2023 Academic Year increases.